Reosquido Desalinasi Metode Evaporasi dengan Ultraviolet Berbasis Mikrokontroller - Azis, Muhammad Abdul; Fajaryati, Nuryake (Elinvo (Electronics, Informatics, and Vocational Education), 2018)
This research aims to create a Reosquido desalination tool for evaporation methods using a microcontroller. This tool can control the temperature to speed up the evaporation process in producing fresh water. The method applied to Reosquido desalination uses Evaporation. The first process before evaporation is the detection of temperature in sea water that will be heated using an element heater. The second process of temperature measurement is to turn off and turn on the Arduino Uno controlled heater, when the temperature is less than 80 ° then the heater is on. The third process is evaporation during temperatures between 80 ° to 100 °, evaporation water sticks to the glass roof which is designed by pyramid. Evaporated water that flows into the reservoir is detected by its solubility TDS value. The fourth process is heater off when the temperature is more than 100 °. Based on the results of the testing, the desalination process using a microcontroller controlled heater can speed up the time up to 55% of the previous desalination process tool, namely manual desalination prsoes without using the heater element controlled by the temperature and controlled by a microcontroller which takes 9 hours. Produces fresh water as much as 30ml from 3000ml of sea water, so that it can be compared to 1: 100.